Effects of urban morphology on microclimate parameters in an urban university campus - Shaikh Salim, Sheikh Ahmad Zaki; Othman, Nurnida Elmira; Wan Ahmad, Siti Wan Syahidah; Mohd Yakub, Mohd Fitri; Muhammad Sukki, Firdaus; Ardila-Rey, Jorge Alfredo; Shahidan, Mohd Fairuz; Mohd Saudi, Ahmad Shakir (MDPI, 2020)
This study investigated the effects of urban morphology on microclimate parameters in an urban university campus in Malaysia. Outdoor air temperatures (Tout) were recorded at eight different locations inside the campus for seven days. The study used three urban morphological parameters such as green cover ratio, height-to-width (H/W) ratio, and sky view factor (SVF). The relationship between urban morphological parameters and Tout obtained from in situ measurements was investigated. The results showed that, at a dense green cover ratio of 22% in a 7833 m2 area where the H/W ratio was 0.2, Tout was reduced by about 1% due to a long building shadow cover (12 h) and a high range of SVF (from 0.61 to 0.68). The use of geographic information system (GIS) to generate the spatial data of Universiti Teknologi Malaysia Kuala Lumpur Campus (UTMKL), morphological features and in situ Tout distributions provided useful information of Tout variations, and proved the applicability of GIS as a useful tool in smart city urban planning.